Commentary on John. - Cyril, Saint, Patriarch of Alexandria, approximately 370-444 (Ancient Christian texts., 2015)
Cyril of Alexandria (ca. 378-444), one of the most brilliant representatives of the Alexandrian theological tradition, is best known for championing the term Theotokos (God-bearer) in opposition to Nestorius of Constantinople. Cyril's great Commentary on John, offered here in the Ancient Christian Texts series in two volumes, predates the Nestorian controversy and focuses its theological firepower against Arianism. The commentary, addressed to catechists, displays Cyril's breathtaking mastery of the full content of the Bible and his painstaking attention to detail as he offers practical teachi.